Implementasi Kebijakan Kawasan Wajib Parkir Elektronik di Kota Semarang - George Natanael Hamonangan Simanjuntak (Journal of Politic and Government Studies, 2026)
The rapid growth of motorized vehicles in Semarang City, exceeding 1.6 million units in 2024, has made the parking sector both a strategic source of locally generated revenue and highly vulnerable to leakage. In response, the Semarang City Government issued Transportation Agency Decree No. 500.11.33/14187 of 2024, designating Jalan MH Thamrin and Jalan Depok as Electronic Mandatory Parking Zones. However, field observations revealed that all parking attendants had reverted to manual systems, indicating a serious implementation failure. This study employed a descriptive qualitative approach using George C. Edwards III's policy implementation theory, examining four variables: communication, resources, disposition, and bureaucratic structure. Data were collected through in-depth interviews with the Head of Parking Section and Field Supervision Team, four parking attendants, and five parking users selected through purposive sampling, supplemented by direct observation and document review with source triangulation. The findings reveal that none of the three main provisions of the Decree were carried out in practice. Most decisive was implementer disposition: parking attendants consciously chose to return to cash transactions because the electronic system threatened their income. This failure is not a technical problem but a social-economic one that requires simultaneous reform of incentive structures, recruitment mechanisms, and supervisory systems.